(untitled) (Journal of Health, Population and Nutrition, 2012)
Low socioeconomic status (SES) is associated with mortality in several populations. SES measures, such as education and income, may operate through different pathways. However, the independent effect of each measure mutually adjusting for the effect of other SES measures is not clear. The association between poverty-income ratio (PIR) and education and all-cause mortality among 15,646 adults, aged >20 years, who participated in the Third National Health and Nutrition Examination Survey in the USA, was examined. The lower PIR quartiles and less than high school education were positively associated with allcause mortality in initial models adjusting for the demographic, lifestyle and clinical risk factors. After additional adjustment for education, the lower PIR quartiles were still significantly associated with all-cause mortality. The multivariable odds ratio (OR) [95% confidence interval (CI)] of all-cause mortality comparing the lowest to the highest quartile of PIR was 2.11 (1.52-2.95, p trend?0.0001). In contrast, after additional adjustment for income, education was no longer associated with all-cause mortality [multivariable OR (95% CI) of all-cause mortality comparing less than high school to more than high school education was 1.05 (0.85-1.31, p trend=0.57)]. The results suggest that income may be a stronger predictor of mortality than education, and narrowing the income differentials may reduce the health disparities. DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11280 J HEALTH POPUL NUTR 2012 Mar;30(1):-82-86